The effect of khat chewing on sexual desire among adults in North East Ethiopia: a propensity score-match analysis - Temesgen Gebeyehu Wondmeneh; Fikre Enquselassie (Frontiers in Public Health)
BackgroundAlthough the number of khat chewers has increased from time to time in Ethiopia, the direction (increased or decreased) of khat chewing on sexual desire is not well known due to the absence of adequate studies. Therefore, this study aimed to assess the effect of khat chewing on sexual desire in adults.MethodsA comparative cross-sectional study was conducted in Logia town. A total of 334 study subjects, comprising 167 khat chewers and 167 non-khat chewers, were included in this study. House-to-house data were collected using the purposive sampling method. To estimate the effect of khat chewing on sexual desire, propensity score matching analysis with a logit model was used to find the average treatment effect (ATE) on the treated and untreated groups. The matching quality was checked statistically and graphically. Logistic regression was used to determine factors associated with sexual desire.ResultsAbout 54.5% of respondents had poor sexual desire. Among khat chewers, 28.1% had poor sexual desire. According to logistic regression analysis, sexual desire was 2.8 times higher in adults aged 18–25 years (AOR = 2.8, 95% CI: 1.02–7.8). Sexual desire was lower in traders (AOR = 0.32, 95% CI: 0.15–0.69), low-income level (AOR = 0.37, 95% CI: 0.16–0.86), and cigarette smokers (AOR = 0.4, 95% CI: 0.2–0.73). There was no significant association between khat chewing and sexual desire (AOR = 0.91, 95% CI: 0.53–1.5). In propensity score matching analysis, the average treatment effect (ATE) on adults who chewed khat was 18.9%, meaning an average increase in sexual desire of 18.9%. The treatment impact on the treated group (ATT) was found to be 24.2%, indicating that 24.2% increased sexual desire among the treated groups (khat chewing).ConclusionMore than half of adults had poor sexual desire. Logistic regression analysis revealed that sexual desire is moderated by age, occupational status, income level, and use of cigarettes. In the propensity score matching analysis, khat chewing can significantly increase the levels of sexual desire.